Penerapan Alat Keran Otomatis pada Gereja Berbasis Arduin Uno dengan Sensor Ultrasonic SR04 - Bintang, Daud; Poningsih, Poningsih; Saputra, Widodo; Sumarno, Sumarno; Lumbantobing, Dedy Kristianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research proposes the application of an automatic tap device at the GBI Tanjung Pasir Church based on an Arduino Uno with an SR04 ultrasonic sensor. Water is the main need for living creatures, especially humans, and most people think that water is a natural resource that is unlimited in quantity. Currently, the operation of tap water is done manually; people often forget to turn off the tap water when the water is full, which causes the water to overflow in the bathtub and waste water in vain, indirectly results in wastage of water, and is very less efficient. An effective way to overcome this is to set the water level limit in the bathtub. In this thesis, an automatic faucet is used using an ultrasonic sensor, namely a sensor that will detect and release or turn off water automatically by activating the primary media using a solenoid valve. The results of this research show that the sensor on the faucet can automatically solve the problem of filling the bathtub when the water level is below a predetermined limit and will stop filling when it reaches the full limit. Having an automatic faucet makes it easier for users to fill and close water without having to monitor it while preventing wastage of water in the bathtub. With an automatic faucet, it is hoped that it can prevent wastage of water in the bathtub due to the user's negligence.